2010
DOI: 10.1111/j.1365-3180.2010.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Weed flora and dormant‐season cover crops have no effects on arbuscular mycorrhizae of grapevine

Abstract: Baumgartner K, Fujiyoshi P, Smith R & Bettiga L (2010). Weed flora and dormant‐season cover crops have no effects on arbuscular mycorrhizae of grapevine. Weed Research50, 456–466. Summary We tested the hypothesis that arbuscular mycorrhizal fungal (AMF) diversity and colonisation of grapevine increase with increasing frequency and diversity of mycorrhizal hosts on the vineyard floor. The vineyard floor cover was manipulated by cover cropping (rye, triticale) inter‐rows, and implementing weed control treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Other studies conducted in maize monocultures have reported AMF richness values which range from 13 species in Minnesota (USA) (Johnson et al 1991;Kurle and Pfleger 1996) Species belonging to what was previously considered the genus Glomus (including genera mentioned above) were most frequent (66.6 % of the total number of AMF species), and most common among the study subplots (FO 050-70 %). These results agree with previous reports from agricultural fields in Europe (Sjöberg et al 2004), Africa (Duponnois et al 2001), and the American Continent (Baumgartner et al 2010;Johnson and Wedin 1997). It has been suggested that species belonging to this genus prevail after soil disturbances because their spores are resistant to the effects of both low-and high-impact practices in managed agroecosystems (Bethlenfalvay 1992).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Other studies conducted in maize monocultures have reported AMF richness values which range from 13 species in Minnesota (USA) (Johnson et al 1991;Kurle and Pfleger 1996) Species belonging to what was previously considered the genus Glomus (including genera mentioned above) were most frequent (66.6 % of the total number of AMF species), and most common among the study subplots (FO 050-70 %). These results agree with previous reports from agricultural fields in Europe (Sjöberg et al 2004), Africa (Duponnois et al 2001), and the American Continent (Baumgartner et al 2010;Johnson and Wedin 1997). It has been suggested that species belonging to this genus prevail after soil disturbances because their spores are resistant to the effects of both low-and high-impact practices in managed agroecosystems (Bethlenfalvay 1992).…”
Section: Discussionsupporting
confidence: 94%
“…Nonetheless, the effect of cover crops on soil community diversity has been scantily studied. For instance, there are few studies on the effect of cover crop use on belowground mutualisms such as plant-arbuscular mycorrhizal fungi (AMF) interactions (Baumgartner et al 2010;Boswell et al 1998;Houngnandan et al 2001;Kabir and Koide 2000), which may in turn also inhibit or reduce the establishment of weeds in crop fields (Jordan et al 2000;Rinaudo et al 2010;Veiga et al 2011). Since most crop species cultivated in the tropics are associated to AMF (Schroeder and Janos 2004) and given the potential role of mycorrhizal interactions in maintaining crop diversity and productivity (Mohammad et al 1998;Oehl et al 2004), it is important to better understand the effect of cover crops on AMF-plant interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Bare reality seems to be more complex as at least two studies give opposite results. On the one hand, Baumgartner et al (2010) revealed that there was no correlation between mycorrhizal colonization of grapevine and frequency of mycorrhizal weeds. The authors suggest that mycorrhizal hosts on the vineyard floor do not significantly influence mycorrhizal colonization or mycorrhizal fungal communities of grapevines.…”
Section: Impact Of Weeds/cover Cropsmentioning
confidence: 94%
“…Studies testing glyphosate effects on AMF show an inhibition of AM fungal spore germination and germ tube growth 34 or reduced mycorrhiza in soil 35 , however only at concentrations greater than those recommended for field use. Several other reports show no effect of glyphosate on mycorrhiza when applied at recommended doses 36 37 38 39 40 . The fate of glyphosate in ecosystems is another aspect which has rarely been investigated 41 42 .…”
mentioning
confidence: 90%